GNSS METEOROLOGY AND LAND SUBSIDENCE OF HEAVY RAINFALL IN JAKARTA ON JANUARY 1, 2020 - Arief, Syachrul; Cahyadi, Mokhamad Nur (Journal of Marine-Earth Science and Technology, 2020)
This study aims to demonstrate that GNSS meteorology can be applied in Indonesia, by estimating the zenith troposphere delay (ZTD) of sustainable GNSS stations in Indonesia, using one of the “goGPS” software packages. As a calculation with rain conditions, the ZTD value was converted into precipitation water vapor (PWV). This research is using GNSS meteorology to be applied into heavy rains at the end of 2019 in Jakarta which was hit by floods on December 31, 2019. According to a report by Geophysical Meteorology and Climatology Agency (BMKG), the main cause of this flood is a high rainfall. The rainfall gauge at Halim Perdanakusuma Station showed 377 mm of rainfall that day. Rain gauges at Taman Mini and Jatiasih stations record rainfall of 335 mm/day and 260 mm / day, respectively. From the GNSS data processing, the PWV values at the five GNSS stations show a similar pattern even though the average between stations is ~ 30 km. The PWV value appeared to be increased at noon on December 30, 2019, and the peak occurs at the end of the day on December 31, 2019. The PWV value showed a sudden drop at midday on January 1, 2020. In the end, the PWV increased again, but not as high as the first peak. From 2 January 2020, the PWV has decreased and has been maintained almost constantly until 4 January. Within this time frame, there were two peak PWV events. The PWV of the first peak was ~ 70 mm and the second peak was ~ 65 mm, and the largest peak PWV was recorded at the CJKT station.